1999
DOI: 10.1097/00007890-199908270-00022
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous Prothrombin Gene Mutation: A New Risk Factor for Early Renal Allograft Thrombosis

Abstract: The prothrombin gene mutation is a new risk factor for thrombotic complications both on hemodialysis and after renal transplantation. It may be useful to screen for this disorder in the pretransplant thrombophilia work-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 17 publications
0
23
0
1
Order By: Relevance
“…There are various risk factors for the occurrence of transplant thromboses. The following factors can have an influence: deceased donation, cold ischaemia time >24 h, multiple transplants, peritoneal dialysis, more than 5 blood transfusions, donor age or recipients <6 years, thrombophilia and low blood pressure during transplantation [4, 7, 17]. In order to avoid thromboses or renal artery stenosis, especially in cases of young recipients (age <9 years), the cold ischaemia time should be as short as possible.…”
Section: Discussionmentioning
confidence: 99%
“…There are various risk factors for the occurrence of transplant thromboses. The following factors can have an influence: deceased donation, cold ischaemia time >24 h, multiple transplants, peritoneal dialysis, more than 5 blood transfusions, donor age or recipients <6 years, thrombophilia and low blood pressure during transplantation [4, 7, 17]. In order to avoid thromboses or renal artery stenosis, especially in cases of young recipients (age <9 years), the cold ischaemia time should be as short as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Prothrombin gene G 20210A polymorphism can be used as a marker for transplant thrombosis as suggested by Oh et al [20] and later confirmed by Fischereder et al [21] and Heidenreich et al [22]. The presence of this mutation in a kidney transplant patient was shown to result in a shorter graft survival (median 65.9 vs 149 months) [21].…”
Section: Thrombophilia (Figure 1)mentioning
confidence: 92%
“…The current evidence implicating the prothrombin gene mutation in complications after renal transplantation is limited to a few case reports and one retrospective study (18,19). Most studies of thrombophilia in renal transplant recipients did not include testing for this mutation.…”
Section: Factor V Leidenmentioning
confidence: 99%